2012
DOI: 10.1111/j.2044-8309.2012.02113.x
|View full text |Cite
|
Sign up to set email alerts
|

Too exhausted to see the truth: Ego depletion and the ability to detect deception

Abstract: In two experiments, recent findings showing the detrimental role of regulatory depletion in decision making are extended to the field of deception detection. In both experiments, the state of ego depletion was induced by having judges inhibit versus non-inhibit a dominant response while transcribing a text. Subsequently they judged true or deceptive messages of different stimulus persons with regard to their truthfulness. In both experiments, ego-depleted judges scored significantly lower on detection accuracy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 60 publications
1
13
0
2
Order By: Relevance
“…For instance, consistent with dual-process theory, people facing higher cognitive load tend to rely heavily on (less valid) nonverbal cues to judge credibility (Reinhard & Sporer, 2008). Moreover, when individuals' cognitive resources are reduced (e.g., by an ego depletion task), they experience more difficulties to analyze verbal cues and achieve lower detection accuracy (Reinhard, Scharmach, & Stahlberg, 2013). Similarly, individuals with high need for cognition (i.e., with a higher motivation to engage in effortful cognitive endeavors) do engage in systematic information processing when facing low (vs. high) cognitive load and are better at detecting deception (Reinhard, 2010).…”
Section: Cognitionsmentioning
confidence: 79%
“…For instance, consistent with dual-process theory, people facing higher cognitive load tend to rely heavily on (less valid) nonverbal cues to judge credibility (Reinhard & Sporer, 2008). Moreover, when individuals' cognitive resources are reduced (e.g., by an ego depletion task), they experience more difficulties to analyze verbal cues and achieve lower detection accuracy (Reinhard, Scharmach, & Stahlberg, 2013). Similarly, individuals with high need for cognition (i.e., with a higher motivation to engage in effortful cognitive endeavors) do engage in systematic information processing when facing low (vs. high) cognitive load and are better at detecting deception (Reinhard, 2010).…”
Section: Cognitionsmentioning
confidence: 79%
“…Third, our findings provide a fundament for further research on the types of dishonesty and self‐control resource involvement. Research on ego‐depletion and lying detection showed that people are worse at lie detection when self‐control resources are limited (Reinhard, Scharmach, & Stahlberg, ), and it would be interesting to see whether this relationship holds true regardless of the type of lie.…”
Section: Discussionmentioning
confidence: 99%
“…Since weak ego-depletion effects on performance might be due to unfulfilled requirements for overriding habits during the ego-depletion manipulation task [56, 57, 58], we applied a handwriting task as a well-established and valid ego-depletion manipulation (cf. e.g., [17, 28, 58, 59, 60]) that has also been used to investigate ego-depletion effects in school children (e.g., [18]). All students were instructed to transcribe a text about the history of the city of Mannheim, Germany.…”
Section: Methodsmentioning
confidence: 99%